Two new species of Merostachys (Poaceae: Bambusoideae) from the Brazilian Atlantic forest - Parma, Daniele F.; Pianissola, Evandro M.; Vinícius-Silva, Ronaldo; Clark, Lynn G.; Santos-Gonçalves, Ana Paula (Phytotaxa, 2016)
Two new species, Merostachys ramosa and M. ximenae, from the Brazilian Atlantic forest are here described and illustrated. The species are apparently endemic to Minas Gerais state, with M. ramosa being restricted to the Parque Estadual da Serra do Brigadeiro. The conservation status of each species is examined. A key to all taxa of Merostachys present in eastern Minas Gerais and comments about the species are provided.